Target reliability for bridges with consideration of ultimate limit state. (1st December 2017) - Ghasemi, Seyed Hooman; Nowak, Andrzej S.
Highlights: A new computational approach was introduced to estimate the relationship between the initial cost and reliability index for structures. As a result, for the non-composite steel girder bridges, a linear relationship between the reliability index and initial cost was observed. This research proposed the failure cost based on the initial cost. The supporting idea behind this recommendation stems from the general economic failure cost, which can be the same as the initial cost. A new generation of the time-dependent objective function was proposed to determine target reliability with regard to construction cost, failure cost, maintenance cost, structural life-time, inflation rate, structural importance factor, and time-dependency of the load and resistance. The structural importance factor, S I, was deliberated as an adjustment factor for the failure cost. Using the contour concept, the influence of S I on the target reliability was illustrated. As expected, a higher value of S I requires the larger the target reliability. The target reliability for non-composite steel girder bridges was determined for bridges with various span lengths, with consideration of the structural deterioration due to the corrosion conditions. It was observed that for the severe corrosion conditions the larger target reliability is required. Abstract: The target reliability is a design constraint that assures the required safety level for structures. Derivation of the target reliability is a complicated and challenging task. To determine the target reliability, two main approaches can be considered. The first approach is based on engineering judgment with respect to past observations of structural failure, while the second method is based on optimization theory. In the past, structural design codes implicitly assumed the target reliability with regard to past experiences, however, the objective of the optimization approach is to compute the target reliability using minimization of the cost-failure function. This contribution attempts to establish an optimization procedure to determine the target reliability for structures with consideration of the construction cost, failure cost, maintenance cost, structural life-time, discount rate, time-dependency of the load and resistance, and structural importance factor. Accordingly, the relationship between, target reliability, structural cost, structural importance factor, and structural life-time are depicted using the contour concept. Eventually, the target reliability for steel girder bridges is determined concerning the ultimate limit state.